DESIGN AND DEVELOPMENT OF AN INTERNET OF THINGS-BASED MONITORING SYSTEM FOR PULLET CHICKENS COOP - Madukara, I Made; Desnanjaya, I Gusti Made Ngurah; Hartawan, I Nyoman Buda; Ekayana, Anak Agung Gde; Adnyana , I Gede (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Pullet chicks require optimal care from hatching to 17 weeks to ensure healthy growth and minimize farmer losses. Traditional coop monitoring systems face significant limitations, including the lack of real-time tracking, automation, and reliance on manual observations, which are prone to errors. This study develops an Internet of Things (IoT)-based coop monitoring system to address these challenges by tracking environmental conditions in real-time using WiFi connectivity through the Research and Development (R&D) method. The system integrates NodeMCU ESP32, DHT22 sensor, MQ-135, anemometer, relay, lamp, 20x4 LCD, and a MySQL database, programmed with PHP and Kotlin. Testing results demonstrate that the system accurately records environmental data over thirteen days, generating 1,897 entries at 10-minute intervals. The recorded temperature ranged from 27.01°C to 31.98°C, humidity from 78.45% to 94.23%, ammonia gas levels from 0.96 ppm to 1.81 ppm, and wind speed from 0.01 m/s to 1.29 m/s. The automatic heating system performed optimally, activating below 28°C and deactivating above 28°C, ensuring stable coop temperatures. This system provides real-time environmental monitoring and automated controls, addressing the limitations of traditional systems. It offers a practical solution for enhancing pullet coop management, with significant potential for broader implementation in poultry farming.